FUNGSI MUSIK RITUAL BRENDUNG DI DESA LANGENSARI KECAMATAN KESESI KABUPATEN PEKALONGAN - Amanu Saputro; Sigit Setiawan (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2024)
Brendung is a ritual carried out by the people of Langensari Village, Kesesi District, Pekalongan Regency to ask for rain during the prolonged dry season. Brendung is a ritual of asking for rain in the form of chanting spells in a song form accompanied by musical instruments from kitchen utensils and puppet as a symbol of Mbak Ayu Brendung which is believed to have a harvest of bringing rain. The brendung ritual is usually held on the day of kliwon in the Javanese calendar, starting from the process of stealing dippers made of coconut shell, assembling and making up dolls, placing dolls in tombs, and ritual processions. Villagers use klothekan for the music such as simple home appliances such as boyong, buckets, trays, cans, and pockets. The uniqueness of brendung music is that it is required to use boyong as its musical instrument. There are three spells in the brendung ritual procession, namely the frankincense burning spell, the song spell, and the closing spell to neutralize the puppet. Brendung music has an important function in the implementation of brendung rituals. The functions of music include the attestation function of social institutions and religious ceremonies, the contribution of social integration, physical reactions, means of communication, social norms, and entertainment.